In AP, the nth term is calculated as:
An = A1 + (n-1)D, where D is the common difference

Using the same,
Let a be the first term in the AP, i.e A1. Then,
a = A1
b = A1 + 1*D = A1 + D
c = A1 + 2*D = A1 + 2D
d = A1 + 3*D = A1 + 3D
e = A1 + 4*D = A1 + 4D

Simultaneous eqn – iii Solve the following simultaneous equations Rate the problemSpam (0)Hard (0)Helpful (0)Wow (0) :52:33+00:00RajniAlgebraArithmeticSolve the following simultaneous equationsRajni Sahsah.rajni@yahoo.comAdministratorSOLVE - ΜΔΓΗŠ

How many coins can cover the entire table? A rectangular table has 100 coins placed on it (centers must be on the table) such that none of the coins overlap, and it is impossible to place any...

Calculate the amount paid in each installments An Electrical shop sells a video recorder for $3200 cash price. The purchase deal is offered to a customer at an extra 20% cost. The customer pays a deposit...

Simultaneous eqn – ii 3x + 4y -2z = 5 x – 3y – 3z = 4 2x – y – 4z = -8 Find x, y and z Rate the problemSpam (0)Hard (0)Helpful (0)Wow (0) :37:00+00:00RajniAlgebraArithmetic3x...

Distance Time A cargo plane flew from the Clark across the Pacific at 255 kph and flew back to the Clark at 275 kph. Given that the first trip took 2...

In AP, the nth term is calculated as:

An = A1 + (n-1)D, where D is the common difference

Using the same,

Let a be the first term in the AP, i.e A1. Then,

a = A1

b = A1 + 1*D = A1 + D

c = A1 + 2*D = A1 + 2D

d = A1 + 3*D = A1 + 3D

e = A1 + 4*D = A1 + 4D

To find, a – 4b + 6c – 4d + e

a – 4b + 6c -4d + e

= A1 – 4(A1+D) + 6(A1+2D) – 4(A1+3D) + (A1+4D)

= A1 – 4A1 – 4D + 6A1 + 12D – 4A1 + 12D + A1 + 4D

= 0